Across boundaries essays in honour of Robert A. Young - Blais, André 1947-; Clercy, Cristine de; Esselment, Anna Lennox; Wintrobe, Ronald 1944- (McGill-Queen's University Press, 2021)
"Why and how does secession happen? How do different levels of government interact with each other? Why do some multi-level governments work better than others? What makes political extremism so virulent in today's society? These are some of the most pressing questions in political science today. These questions and research areas - secession, multi-level government, and political economy -were the focus of the writing and scholarship of Robert (Bob) Andrew Young (1950-2017), Canada Research Chair in Multi-Level Governance at the University of Western Ontario and one of Canada's most distinguished political scientists. In Across Boundaries Young's former colleagues and students bring together contributions from his extensive network, which included academics, government officials, and media personalities. These essays speak to Young's legacy while providing new insight into research in multi-level governance, secession, and political economy. Young's body of work is exemplary in its attention to concrete policy issues as well as in the breadth of his interest across many subfields of political science. Across Boundaries honours his distinguished career and gives students, professors, and practitioners further insight into his scholarship."--
Keywords: Young, Robert Andrew -- 1950-2017; Föderalismus; Politik; Sezession -- Völkerrecht; Politische Ökonomie; Politische Wissenschaft; Kanada; Political science; Federal government; Central-local government relations; Secession; Economics; Festschrift